Effect of organic based fertilizer from tropical peat on selected crop - Mohd Shuib, Effyanti (2015)
Fertilizers have important elements which promote plant growth and development. Currently, chemical fertilizers are preferred in agriculture because of their effectiveness, abundance, and high nutrients content, as compared to natural or organic fertilizers. However, the increased use of chemical fertilizers has been implicated in human health and environmental quality. Thus, less harmful fertilizers are needed in modern agriculture as an alternative of chemical fertilizers. Application of humic fractions mixture as a fertilizer could be useful in promoting plant growth and selected soil chemical properties. Furthermore, there is dearth of information on the effects of this fertilizer on crops growth and development. Thus, three studies were conducted to determine the: (i) effects of urea and rock phosphate (RP) on selected soil properties, (ii) effects of humic fractions isolated from a tropical peat on N, P and K availability in an acidic soil, and (iii) beneficial use of humic fractions mixture (fertilizer) on Zea mays growth and nutrients uptake. Two incubation studies were set up in the soil laboratory of Universiti Putra Malaysia Bintulu Campus, Sarawak Malaysia. Both studies were carried out for 50 days due to the necessity of the data for greenhouse evaluation of promising treatments. Zea mays was selected as a test crop because of its sensitivity to nutrients deficiency. For the first study, the initial effects of urea and Christmas Island rock phosphate (RP) fertilizers on soil chemical properties were determined using standard procedures. Results in this study showed that the rates of 1, 1.5, and 2 g urea and incubation periods of 0, 10, 20, 30, 40 and 50 day did not affect soil pH (in both water and KCl) except for day 40 and day 50. Although the soil pH increased after surface application of urea, the changes were not obvious between rate and incubation period. The dissolution rate of urea could be one of the reasons for this finding. As reported by a number of researchers, under favourable conditions, urea rapidly dissolves in soils within 7 days of application such that ammonia volatilization peaks at 3 to 4 days. As a result, there was increase of NH4+ and NO3- contents in the soil. For RP, the highest rate (2 g) temporary delayed the increase of available P content in the soil. The low dissolution rate of RP might have occurred at the early stage of application. Initially, dissolution of RP caused significant amount of Ca and P, and this continued until the concentration of Ca and P reached saturation level. In the second experiment, crude humic (HA) and fulvic acids (FA) were used to enhance the availability of N and P in soil. The seven treatments evaluated in this study were as follows: T1 (2 g HA + 0.75 g urea + 2 g RP), T2 (2 g HA + 1.5 g urea + 2 g RP), T3 (2 g HA + 2.25 g urea + 2 g RP), T4 (10 mL FA + 2.25 g urea + 1 g RP), T5 (10 mL FA + 2.25 g urea + 1.5 g RP), T6 (10 mL FA + 2.25 g urea + 2 g RP) and T7 (2 g HA+ 10 mL FA + 1.5 g urea + 1 g RP). T4 and T5 showed significantly higher soil pH value as compared to other treatments. A similar result was observed for soil exchangeable NH4+. This suggesting the role of FA in controlling soil pH and NH4+. This observation is related to the negative charges and the solubility of the FA. To further evaluate the promising treatments in the incubation studies, a pot study was conducted for 52 days (tasseling stage of maize). Six treatments were evaluated: T0 (no fertilizer added), T1 (4.13g urea + 1.52g TSP + 1.34g MOP), T2 (2g HA + 1.5g urea + 2g RP), T3 (2g HA + 2.25g urea + 2g RP), T4 (10 mL FA + 1.5g urea + 1g RP), T5 (10 mL FA + 2.25g urea + 1.5g RP) and T6 (2g HA + 10 mL FA + 1.5g urea + 1g RP). The treatments were applied at 10 and 28 days after planting (DAP). Soil and plants samples were sampled at 52 days after planting after which the samples were analyzed using standard procedures. Application of humic mixture significantly increased soil pH. T5 was effective in increasing soil NH4+ content whereas T3 showed the highest content of NO3-, available P, and exchangeable cations. T2 was superior in promoting plant height and dry weight. The molecular weight of humic and fulvic acids could be associated with this observation. On the other hand, the ratios of N and C in these two compounds may also have affected the results. The high C/N ratio of fulvic acid causes chelation of N compounds, such as NH4+ whereas lower C/N ratio caused NH4+ to be in the form of soluble or exchangeable in soil. Besides, HA is classified as hormone-like materials or compounds and these properties are useful in promoting plant growth. Applications of crude humic and fulvic acids had effect on the amount of N and P in soils such that their availability increased in the soil. Abundance of negatives charges in both humic fractions promoted the availability of N and P in the soil system. This enhanced Zea mays plant growth, and nutrients uptake. However, at least three cycles of a field study need to be carried out in the future to validate the findings of this study.